Nadir kay dost - Maryam, Shera; Shireen, Syed (book group Karachi, 1998)
Nadir Kay Dost (Nadir's Friends) is a popular Urdu children's book that introduces young readers to the concept of friendship. The book likely follows the story of Nadir and his friends, exploring their adventures, shared experiences, and the importance of loyalty and kindness.